Human Papillomaviruses and Papillomatosis Lesions of the Female Lower Genital Tract - Yu-Liang Fu; Yao-Xiong Hu; Han-Liang Ling; Zhen-Zhong Ye; Tian Liang; Mei-Gui Zhang; Yun-Ke Liu; Biao Kang; Yuan-Ji Luo; Shu-Ying He; Yong-Jian Lian (Hindawi Limited, 1994)
Objective: The objective of this study was to determine whether human papillomavirus (HPV) infections are involved in the development of papillomatosis lesions of the lower female genital tract.